Research in personnel and human resources management. Volume 33 - Buckley, M. Ronald; Wheeler, Anthony R.; Halbesleben, Jonathon R. B. (Research in personnel and human resources management., 2015)
This series publishes original monograph length conceptual papers, written by exceptional scholars, designed to promote theory and research on cutting edge substantive and methodological issues in the field of human resources management. Volume 33 of Research in personnel and human resources management (RPHRM) contains six papers on salient issues in the field of human resources management, thus continuing in the tradition of the series to develop a more informed understanding of this field. The subject matter in this volume covers myriad areas: employee maintenance, the resignation process, ethics in human resources management, diversity climate, occupational safety, and organizational justice. These papers, written by some of the finest scholars in the field, represent seminal scholarly advances and illustrate the interdisciplinary character of human resources management.